Global Perspectives on Catholic Religious Education in Schools: Volume II: Learning and Leading in a Pluralist World - Buchanan, Michael T.; Gellel, Adrian-Mario (Springer eBooks Education, 2019)
Part I Theoretical Issues -- 1 The Teacher of Religion: Choosing between Professions in Catholic Schools -- 2 Catholic Religious Education: Educating for Faith -- 3 The Challenges of Integrating Catholic Religious Education and Catechesis: An American Quandary? -- 4 Rethinking Catholic Religious Education in the Light of Divine Pedagogy -- 5 New Wine in Fresh Wineskins. Rethinking the Theologicity of Catholic Religious Education -- 6 Theological Underpinnings of Australian Catholic RE: A Public Theology Proposal -- 7 The Religious Education of the Religion Teacher in Catholic Schools -- 8 Moral Formation in Catholic Religious Education: Insights from the Fourth Gospel -- 9 Von Balthasar's Theo-Aesthetics Applied to Religious Education -- 10 Primary School Parents' Perspectives on Religious Education -- 11 Examining School and Parish Interaction: Some Implications from Religious Education -- Part II Teacher Formation and Professional Development -- 12 The Transmission of Religion: Reconceptualising the Religious Education Leader -- 13 Confident Student to Confident RE Teacher: A Perspective from Scotland -- 14 Formation for MissioN: A systems Model within the Australian Context -- 15 Catholic Teachers, Theological Literacy and Engagement with Biblical Texts -- 16 Teacher Readiness: A Pedagogy of Encounter -- 17 A Pilgrimages: Fruitful Sources of Faith Formation for Catholic Student Teachers? -- 18 Teacher as Expert: Using Teacher Knowledge to Engage Students -- 19 A CPD and RE: What do RE Teachers in Irish Catholic School Say -- 20 Pedagogical Content Knowledge: A Missing Piece in the Puzzle that is Religious Education in Catholic Schools -- Part III Pedagogical and Content Issues -- 21 Early Childhood Religious Education: It Matters, but What is its Matter? -- 22 Catholic Early Years Educators' Dilemma: Remaining Faithful to Children's Spiritualities -- 23 God, the Church and Today's Child: Cavalletti in the Classroom? -- 24 Effective Tools for Pedagogical Change in Religious Education: Experience of Teachers in Hong Kong Catholic Kindergartens and Primary Schools -- 25 Enhancing Curriculum Syllabi and Frameworks: Catechetical, Cognitive, and Affective Principles -- 26 Religious Arts and Liturgical Catechesis of Children -- 27 Education through Art: The use of Images in Catholic Religious Education -- 28 From Early Christian Art to Postmodern Visual Imaginary: New Approaches to Catholic Religious Education -- 29 Storying Faith: The Promises and Contradictions of New Media in Catholic Religious Education -- 30 Using Digital Technologies to Interpret Life: Media Literacy and Catholic Religious Education in Dialogue -- 31 Contextual Influences on KNowledge Mediation in Religious Education and its Significance for Teacher Education -- 32 Catholic Social Teaching, Catholic Education and Religious Education -- 33 The Anthropological Dimensions of the Preparation of Youth for Marriage and Family -- 34 Stewards of Creation: Laudato Si', Ecological Conversion and Religious Education -- 35 Engagement in Religious Education: Focusing on Spiritual and Religious Capabilities -- 36 Integrating Community Spirituality into Religious Education: A School Educator's Role -- 37 Applying René Girard's Mimetic Theory in the Religious Education Classroom -- 38 Profiling and Enhancing Religious Education in Catholic Schools -- 39 How do Sport Educator-Coaches Contribute to RE in Catholic Schools? -- Part IV Inter-Religious Issues -- 40 Teaching about Religious Diversity: Policy and Practice from the Council of Europe -- 41 Religious Education: A Creative Time and Space for Spiritual Development -- 42 The Student Voice in South African Catholic School Religious Education -- 43 Pedagogical Identity for Religious Education in Catholic Schools: A Brazilian Case Study -- 44 A Panorama of Christian Religious Education Education in Nigeria -- 45 Identity and Dialogue: Learning from a Personal Interreligious Encounter -- 46 Catholic Religious Education in Germany and the Challenges of Religious Plurality -- 47 Interreligious Education Involving Christianity and Confucianism in Hong Kong -- 48 A Theory of Alterity as a Perspective for Interreligious Learning -- Part V Contextual Issues -- 49 Policies to Reform Religious Education in Hong Kong Catholic Schools -- 50 Catholic Youth Associations' Activities in All-Day Schools in Germany: Opportunities and Limits -- 51 The Medellín Path in the School Institution: The Chilean Case -- 52 Religious Education in the Secularized Netherlands